‫التنظيم ‬‫المهني‬ ‫للمراجعة‬ ‫الخارجية‬ ‫في‬ ‫الجزائر‬ ‫وأثره‬ ‫على‬ ‫تطو‬ ‫رها‬ ‫دراسة‬‫ميدانية‬ - ‫شعلان ‬‫سوميـة‬; ‬‫إينـاس ‫ بلكيـراد ‬ (My University, 2018)
The study dealt with the impact of the professional organization of the external audit in Algeria on its development. The external audit was discussed through presentation of its concept and its significance, objectives, hypotheses and various practical steps to achieve them, as well as recognition of international auditing standards, and give a picture and stand on the professional reality of auditing in Algeria. . The analytical descriptive method was used to conduct the study by collecting data from secondary and primary sources obtained through the distribution of questionnaire lists to a sample of the study's 46 population, which included accountants, certified accountants, auditors, and university professors, and then we have compiled and compiled data and unloaded and analyzed using the program spss. This study found that the current organization of the auditing profession in Algeria does not have many characteristics and requirements to develop the profession. ........................................................ تناولت الدراسة أثر التنظيم المهني للمراجعة الخارجية في الجزائر في تطورها. تمت مناقشة التدقيق الخارجي من خلال العرض التقديمي له المفهوم وأهميته وأهدافه وفروضه والخطوات العملية المختلفة لتحقيقه لهم، فضلا عن الاعتراف بمعايير التدقيق الدولية، وإعطاء الصورة والموقف الواقع المهني لمراجعة الحسابات في الجزائر. . وتم استخدام المنهج الوصفي التحليلي لإجراء الدراسة من خلال جمع البيانات من المصادر الثانوية والأولية التي تم الحصول عليها من خلال توزيع قوائم الاستبيان على أ عينة من مجتمع الدراسة البالغ عددها 46 مجتمعاً، والتي شملت المحاسبين والمحاسبين القانونيين، المراجعين، وأساتذة الجامعات، ومن ثم قمنا بتجميع وتجميع البيانات و وتفريغها وتحليلها باستخدام برنامج spss. وقد توصلت هذه الدراسة إلى أن التنظيم الحالي لمهنة مراجعة الحسابات في الجزائر ليس كذلك لها العديد من الخصائص والمتطلبات لتطوير المهنة.